2016
DOI: 10.1007/7854_2016_31
|View full text |Cite
|
Sign up to set email alerts
|

Does Diet Matter? The Use of Polyunsaturated Fatty Acids (PUFAs) and Other Dietary Supplements in Inflammation-Associated Depression

Abstract: An increasingly pertinent issue in psychiatry in recent years is that of the limitations of conventional antidepressants, which are not effective in a large number of patients with major depressive disorder (MDD). Coupled with emerging hypotheses about the role of inflammation in depression, it would appear that it is time to look for alternative treatments for these symptoms.This review will examine an emerging area in psychiatry, that of dietary supplements and the diet in general to treat depressive symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 107 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…With diet as a modifiable factor, limiting pro-inflammatory diets and/or favouring anti-inflammatory diets may be an approach for preventing depression and reducing depressive symptoms. For example, dietary supplementation with PUFA could improve inflammation-associated depressive symptoms ( 34 ) . In addition, nutritional interventions targeting the gut microbiota also could modulate depression ( 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…With diet as a modifiable factor, limiting pro-inflammatory diets and/or favouring anti-inflammatory diets may be an approach for preventing depression and reducing depressive symptoms. For example, dietary supplementation with PUFA could improve inflammation-associated depressive symptoms ( 34 ) . In addition, nutritional interventions targeting the gut microbiota also could modulate depression ( 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various inflammatory cytokines, such as TNF-α and IL-6, have been reported to be involved in the occurrence and development of ALD (27,28). Previous studies have shown that glutamine and probiotics reduce inflammation, promote the secretion of anti-inflammatory cytokines and maintain intestinal barrier functions (29,30). The present results demonstrated that probiotic and glutamine treatments reduced the abnormally elevated serum IL-6 and TNF-α levels following chronic ethanol consumption, demonstrating that probiotics and glutamine likely alleviated hepatic inflammation via the suppression of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…From a biological point of view, various hypotheses have been formulated. A healthy diet may positively affect mood by increasing brain levels of monoamines [ 42 ], reduce apoptosis of the limbic system [ 43 , 44 ], and have anti-inflammatory properties [ 45 , 46 ]. The high content of antioxidants in fruits and vegetables is likely to be protective against the negative effects of oxidative stress at neuronal level, which has been associated with depression [ 47 ].…”
Section: Discussionmentioning
confidence: 99%